Effect of E-Tax Payment on Revenue Generation in Nigeria - OLAOYE, Clement Olatunji; ATILOLA, Oluseyi Olabanji (Journal of Accounting, Business and Finance Research, 2018)
The study examined the effect of e-tax payment on revenue generation in Nigeria. The study period covered six (6) years and three (3) quarters, spanning from the first quarter of 2012 to the second quarter of 2018. the period for pre e-taxation covered thirteen (13) quarters, spanning from the first quarter of 2012 to the first of 2015 while the period for post e-taxation covered thirteen (13) quarters, spanning from the second quarter of 2015 to the second quarter of 2018.The analysis was carried out using Trend analysis, descriptive statistics of mean and standard deviation, paired sampled t-test. The findings revealed that there was insignificant positive difference between pre and post value added tax revenue with t-statistics and p-value of 0.520 and 0.612 respectively. This connotes that e-tax payment has an insignificant positive effect on value added tax revenue in Nigeria. Similarly, it was discovered that there was a positive insignificant difference between pre and post company income tax revenue with t-statistics and p-value reported to be 0.833 and 0.421 respectively. That is, e-tax payment has negative insignificant impact on Value Added Tax (VAT) revenue. Lastly, the findings revealed that there is a positive insignificant difference between pre and post capital Gain tax revenue with t-statistics and p-value of 1.218 and 0.247 reported to be respectively. That is, that e-tax payment has a positive insignificant effect on company income tax revenue in Nigeria. It was therefore concluded that E-tax payment has not contributed to capital gain tax, value added tax and company income tax generation in Nigeria.